Synthesis, Optical and Photocatalytic Properties of ZnSe Microspheres/Nanosheets - Yongqiang Yang; Yan Zhang; Xuejiao Zhou; Xiaochen Wu; Sizhe Xu; Haixia Wu; Shouwu Guo (Nano Biomedicine and Engineering, 2011)
The microspheres/nanosheets of the ZnSe were prepared by solvothermal route. The morphological, structural, optical, as well as photocatalytic properties of the ZnSe products were studied. SEM and TEM results showed that morphologies of the products were sensitive to the presence of water or not, and a mechanism was proposed. The products shows a weak blue emission band centered at 476 nm, which is attributed to the near-bandedge emission of the products, and the strong and broad peak at 520 nm is attributed to a defect-related emission. The PL and XRD results indicate that ZnSe microspheres have high crystalline and few defects compared with ZnSe nanosheets, the degradation for Rhodamine 6G shows that the photoactivity of ZnSe nanosheets is nearly twice that of ZnSe microspheres. Therefore, the decrease of defects implies the decrease of photocatalytic activity, and nanosheets is more suitable for the degradation of Rhodamine 6G.